The Effects of the Solvent Choice of the Continuous Phase on the Poly(Urea-Urethane) Microcapsules Properties - Salaün, F. (Journal of Chemical Engineering Research Updates, 2020)
Xylitol, a natural crystalline polyol, presents a cooling effect due to its negative heat of solution at 35 °C supported by humidity absorption, contributing to a fresh sensation when it dissolves. Since this material is sometimes in a liquid state, it cannot be incorporated in or onto a substrate without being protected. One of the strategies to protect the active substance may be forming a barrier layer at its surface, i.e., microencapsulation. The present work is devoted to studying the effect of continuous phase parameters affecting on encapsulation of xylitol with a poly (urea-urethane) shell through a two-step microencapsulation process. The first step is liquid-liquid dispersion either in toluene or Miglyol 812N, and the second step is microencapsulation by interfacial polymerization. The process can be used to control the size distribution of the microparticles, the thickness, and the chemical nature of the shell, which influences the release rate of the active substance. The choice of the continuous phase solvent (toluene or Miglyol 812N) required some changes in the formulation of the system, especially the HLB of the surfactant mixture, to obtain a stable emulsion with a narrow particle size distribution. The thermo-chemical and morphological characteristics of microparticles were studied by Fourier transform-infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), enthalpy of dilution, and scanning electron microscope (SEM). The microparticle size is governed by the emulsion step and the chemical composition of the organic phase. Most of the thermal properties are related to their porous structure and their chemical shell formation during the interfacial polymerization step.